Dickens, Religion and Society - Butterworth, Robert; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Dickens, Religion and Society examines the centrality of Dickens's religious attitudes to the social criticism he is famous for, shedding new light in the process on such matters as the presentation of Fagin as a villainous Jew, the hostile portrayal of trade unions in Hard Times and Dickens's sentimentality.
Keywords: Literature; Religion and sociology; Literature -- History and criticism; Literature, Modern -- 19th century; Fiction; European literature; British literature; Literature; British and Irish Literature; Religion and Society; Nineteenth-Century Literature; Literary History; Fiction; European Literature; Electronic books